Phonon engineering in proximity enhanced superconductor heterostructures - Yong-Chao Tang (Nature Portfolio, 2017)
Abstract In this research, we tailor the phonon density of states (DOS) in thin superconducting films to suppress quasiparticle losses. We examine a model system of a proximity-enhanced three-layered Al/Nb/Al heterostructure and show that the local quantized phonon spectrum of the ultrathin Al cladding layers in the heterostructure has a pronounced effect on the superconducting resonator’s quality factors. Instead of a monotonic increase of quality factors with decreasing temperatures, we observe the quality factor reaches a maximum at 1.2 K in 5/50/5 nm Al/Nb/Al microstrip resonators, because of a quantized phonon ladder. The phonon DOS may be engineered to enhance the performance of quantum devices.